Time programmed feed of semi-batch reactors with non-linear radical copolymerizations: an experimental study of the system styrene + divinylbenzene using SEC/MALLS - Gonçalves, Miguel A.D. (2007)
The radical crosslinking copolymerization of mono and divinyl monomers was experimentally studied with a 2.5 dm3 semi-batch reactor using styrene + divinylbenzene as a model system. The analysis of products was carried out by SEC with a MALLS detector. The influence of the feed policy of divinylbenzene on the time evolution of the copolymer molecular weights and z-average mean square radius of gyration was assessed. A detailed kinetic model, in the absence of intramolecular reactions but taking into account the presence of the two isomers m- and p- in the commercial divinylbenzene and the different reactivities of the various radicals and double bonds was developed; most parameters have been collected from previous kinetic studies, and only two have been regressed using our measured molecular weights. These results can be used to improve the production of branched/crosslinked polymers with controlled molecular architecture.